Partial capability loss through MEADS - Sascha Lange (Stiftung Wissenschaft und Politik (SWP), 2005)
The still-to-be-developed air-defense system, MEADS, is supposed to replace the adopted Patriot System by 2015. The announced aim is an improvement of Germany's and its armed forces' protection as well as the protection of its allies and their armed forces while abroad. Can the future Medium Extended Air-Defense System meet these demands? What are the advantages and disadvantages of MEADS? Are more suitable solutions obtainable? (SWP-Comments / SWP)
Keywords: 320